2019
DOI: 10.1155/2019/6517839
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Cassava (Manihot esculenta) Peels as a Dietary Supplement in Tropical Friesian Holstein Cross Breed Dairy Cattle

Abstract: Cassava (Manihot esculenta) Peels supplementation in feed was evaluated on quality and quantity of dairy cattle production. Cassava peels were waste product of tapioca flour industry. A total of 26 lactation dairy cattle breed Friesian Holstein cross breed maintained at individual cage at farm on Kawi Mountain, Malang, East Java. It was randomly allotted to treatment and control group (13 head of cattle in each group). Treatment group were fed with cassava peels base dietary, whereas control group were fed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although there were differences in the consumption of NDF, a precursor of milk fat, the production of acetic acid in the rumen may not have differed between diets. Pertiwi et al [ 58 ] concluded that supplementation with 34.5% cassava root husk in Holstein cows positively affected CP and total solids. Their results for fat and milk volume were similar to those of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were differences in the consumption of NDF, a precursor of milk fat, the production of acetic acid in the rumen may not have differed between diets. Pertiwi et al [ 58 ] concluded that supplementation with 34.5% cassava root husk in Holstein cows positively affected CP and total solids. Their results for fat and milk volume were similar to those of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cassava peels, a waste product of tapioca flour industry is usually discarded while processing. Studies were made by Pertiwi et al (2019) on supplementation of this discarded cassava peels with feed. Cattle population were grouped and fed with the discarded cassava peel-based feed and the quality of milk was assessed.…”
Section: A) Livestock Feedmentioning
confidence: 99%
“…Tannins are polyphenols that alter appetite and absorption directly or indirectly (12). In dairy cattle, tannin has a beneficial effect to increase the quality of milk produced (13). In contrast to ruminant animals, poultry lacks bacteria in their gastrointestinal tract that detoxify or reduce the effect of tannins, it generates compounds with proteins and carbohydrates or blocking digestive enzymes, Therefore by this mechanism, tannins decreased growth and feed efficiency.…”
Section: Production Performancementioning
confidence: 99%